Analisis Body Composition pada Member Private Rayatama Fitness Center (Lembaga Pengembangan Kinerja Dosen, 2026)
Urban lifestyle changes have increased public awareness of health, reflected in the growing number of fitness centers. However, many gym members still regard body-weight reduction as the sole indicator of training success, even though body weight does not always reflect physiological change during training. This study aimed to analyze and describe the body composition profile of members at Rayatama Fitness Center, Ngoro, Jombang, and to examine differences between male and female members. A quantitative descriptive method was used with a purposive sampling technique involving 20 subjects (10 men and 10 women, aged 25–35 years). Physical data were collected using a Bioelectrical Impedance Analysis (BIA) device (Omron Karada Scan HBF-375), covering body weight, Body Mass Index (BMI), body fat, visceral fat, subcutaneous fat, skeletal muscle mass, and basal metabolic rate (BMR). Results show that most members fall into the overweight-to-obese category based on BMI and generally have low skeletal muscle mass. Male members show higher visceral fat, while female members show higher body fat and subcutaneous fat percentages. These findings suggest BIA-based assessment should be used as routine evaluation to design more individualized training programs.